Do we get worried sick? An answer from the Psiconeuroinmunoendocrinology - Yolanda Cabrera Macias (Medisur, 2017)
The Psychoneuroimmunoendocrinology studies the interaction between psychic processes and the Nervous, Endocrine and Immune systems and, in an integrative way, the health-disease process interrelationships. Several researches show the close relation between the somatic diseases emergence and development with certain psychological alterations, among them stress, anxiety and depression. This work is aimed at systematizing the theoretical elements which demonstrate the interrelation between the psyche, the Nervous System, Endocrine and Immune System in the health - illness process and to present the clinical evidences which support its validity.